Hepatoprotective effect and structural analysis of Hedysarum polysaccharides in vivo and in vitro. Issue 8 (28th April 2022) - Wang, Donghan; Xue, Zhiyuan; Wu, Huifang; Shi, Gengen; Feng, Shilan; Zhao, Lianggong
Abstract: The crude Hedysarum polysaccharides (HPS: HPS‐50 and HPS‐80) obtained from Radix Hedysari exhibited great pharmacological activities in our previous research. This study investigated the effects of HPS on lipopolysaccharide (LPS)/D‐galactosamine (D‐GalN)‐induced acute liver injury (ALI) in mice and LPS‐induced injury in LO2 cells, as well as the relationship between structural characteristics and hepatoprotective activities. The in vivo results showed that compared with HPS‐80, HPS‐50 showed stronger hepatoprotection, which improved histopathological changes to normal levels. HPS‐50 significantly decreased the levels of ALT, AST, MPO, and MDA, increased the activities of SOD, CAT, and GSH, and suppressed the LPS/D‐GalN‐triggered production of TNF‐α, IL‐1β, and IL‐6 ( p < .05). The results in vitro showed that HPS‐50‐P (HPS‐50‐1, HPS‐50‐2, and HPS‐50‐3) purified from HPS‐50 played significant protective roles against LPS‐induced injury in LO2 cells by reducing cell apoptosis and relieving cell cycle arrest. HPS‐50‐2 restored the percentage of normal cells from 54.8% to 94.7%, and reduced the S phase cells from 59.40% to 47.05% ( p < .01). By analyzing the structure of HPS‐50‐P, including monosaccharide composition, molecular weight, chain conformation, and surface morphology, we speculated that the best protective effect of HPS‐50‐2 might be attributed to its beta configuration, highest molecular weight, and high glucose and galactose contents. These findings indicate that HPS‐50 might be a promising source of functional foods for the protection and prevention of ALI. Practical applications: In this study, the protective effect of HPS on ALI was evaluated from multiple perspectives, and HPS‐50‐2 was screened as a potential active ingredient. This study has two practical applications. First, it provides a new way to improve ALI, and a new option for patients to prevent and treat ALI. Second, this work also complements the pharmacological activity of Radix Hedysari and provides a basis for the development of Radix Hedysari as a functional food. Abstract : HPS had a strong protection on LPS/D‐GalN‐induced ALI, and HPS‐50‐2 was screened as the potential material basis, which might be contributed to its beta configuration, the highest molecular weight, and the high contents of glucose and galactose.